KAPASITAS MASYARAKAT DALAM MENGHADAPI ANCAMAN BENCANA ERUPSI GUNUNG MARAPI DI NAGARI PARIANGAN KECAMATAN PARIANGAN - leony melta putri; Iswandi Umar (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
Abstract This study aims to determine the capacity of the community in dealing with the threat of the eruption of Mount Marapi in Nagari Pariangan, Pariangan District. This study uses a quantitative method using a descriptive approach, this study uses a questionnaire as a research instrument. The population in this study was the community of Nagari Pariangan, amounting to 5,562 people. The subjects of this study were 98 people who were determined by random sampling method. The technique used is descriptive statistical analysis by calculating the percentage. The results of this study are seen from the five Hyogo Frameworks of action or Hyogo Framework. Based on these five parameters, it shows that the community's capacity to deal with the threat of the eruption of Mount Marapi in Nagari Pariangan, Pariangan District, is 64.58% of disaster management rules and institutions in the medium category, early warning is 51.45% in the low category, 47, 76% is about education. in the low category, 48.81% on reducing basic risk factors in the low category, and 56.90% on the development of disaster preparedness in the medium category. With a total percentage of 53.90%, it can be concluded that the community's capacity to face the threat of the eruption of Mount Marapi in Nagari Pariangan, Pariangan District is still relatively low. Therefore, the capacity of the people of Nagari Pariangan must be increased again because based on the results of research, the people of Nagari Pariangan are still not ready to face disasters that can occur at any time. Keywords: Capacity, Public, Merapi Volcano Eruption